Parki kieszonkowe - trend w kształtowaniu przestrzeni miejskiej = Pocket parks - the trend in creating the urban space - Tokarska-Osyczka, Agnieszka; Osyczka, Dominik (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Pocket parks are a response to the current needs of urban residents. The main idea is to use even the smallest space for the green areas and if they are appropriately designed they can fulfill various functions. The article discusses the examples of such mini parks in the world and Poland, focusing on the most important facts about these parks. The paper indicated that they differ among themselves in size, function, selection of species and equipment.
Keywords: parki kieszonkowe; tereny zieleni miejskiej; zieleń miejska; małe przestrzenie; mini parki; pocket park; urban green areas; urban greenery; small spaces; mini-parks